High serum klotho levels are inversely associated with the risk of low muscle mass in middle-aged adults: results from a cross-sectional study - Xie, Yilian; Huang, Kai; Li, Hui; Kong, Weiliang; Ye, Jiayuan (Frontiers in Nutrition, 2024)
Objective: Muscle mass gradually declines with advancing age, and as an anti-aging protein, klotho may be associated with muscle mass. This study aims to explore the relationship between klotho levels and muscle mass in the middle-aged population. Methods: Utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2018, we conducted a cross-sectional analysis on a cohort of individuals aged 40-59. Weighted multivariable analysis was employed to assess the correlation between klotho and low muscle mass, with stratified and Restricted Cubic Spline (RCS) analyses. Results: The cross-sectional investigation revealed a significant negative correlation between klotho levels and the risk of low muscle mass Model 3: OR = 0.807, 95% CI: 0.712-0.915). A notable interaction between klotho and sex was observed, with a significant interaction effect (P for interaction = 0.01). The risk association was notably higher in females. The risk association was notably higher in females. Additionally, RCS analysis unveiled a significant linear relationship between klotho and low muscle mass (P for nonlinear = 0.9495, P for overall＜0.0001). Conclusion: Our observational analysis revealed a noteworthy inverse relationship between klotho and low muscle mass, particularly prominent among female participants. This discovery provides crucial insights for the development of more effective intervention strategies and offers a new direction for enhancing muscle quality in the middle-aged population.